Decreased generation of procoagulant platelets detected by flow cytometric analysis in patients with bleeding diathesis. Issue 6 (12th February 2014) - Daskalakis, Michael; Colucci, Giuseppe; Keller, Peter; Rochat, Sophie; Silzle, Tobias; Biasiutti, Franziska Demarmels; Barizzi, Gabriela; Alberio, Lorenzo
<x xml:space="preserve">Abstract</x> Background A clinically relevant bleeding diathesis is a frequent diagnostic challenge, which sometimes remains unexplained despite extensive investigations. The aim of our work was to evaluate the diagnostic utility of functional platelet testing by flow cytometry in this context. Methods In case of negative results after standard laboratory workup, flow cytometric analysis (FCA) of platelet function was done. We performed analysis of surface glycoproteins Ibα, IIb, IIIa; P‐selectin expression and PAC‐1 binding after graded doses of ADP, collagen, and thrombin; content/secretion of dense granules; and ability to generate procoagulant platelets. Results Of 437 patients investigated with standard tests between January 2007 and December 2011, we identified 67 (15.3%) with high bleeding scores and nondiagnostic standard laboratory workup including platelet aggregation studies. Among these patients, FCA revealed some potentially causative platelet defects: decreased dense granule content/secretion (n = 13); decreased α‐granule secretion induced by ADP (n = 10), convulxin (n = 4), or thrombin (n = 3); decreased fibrinogen receptor activation induced by ADP (n = 11), convulxin (n = 11), or thrombin (n = 8); and decreased generation of COAT platelets, that is, highly procoagulant platelets induced by simultaneous activation with collagen and thrombin (n = 16). Conclusion Our work confirms that storage pool defects are frequent in patients with a bleeding diathesis and normal coagulation and platelet aggregations studies. Additionally, FCA is able to identify discrete platelet activation defects. In particular, we show for the first time that a relevant proportion of these patients has an isolated impaired ability to generate COAT platelets—a conceptually new defect in platelet procoagulant activity, which is missed by conventional laboratory workup. © 2014 International Clinical Cytometry Society